Dental care and HIV-infected individuals: are they equally treated? - Giuliani M, Lajolo C, Rezza G, Arici C, Babudieri S, Grima P, Martinelli C, (Blackwell Synergy, 2005)
To investigate the problems in seeking dental care faced by HIV-positive individuals in Italy.